Social influence and price, influence on consumer resistance to innovation - Abbas, Mazhar; Mohtar, Shahimi (UUM College of Business, 2015)
The basic purpose of this study is to investigate the consumer buying behavior.In this study smartphone used as innovation.In the technological advancement smartphone is best communication tool and playing significant role in the society. In this study researcher identified some factor that influence the consumer buying behavior and consumer always buy new product through focusing all these factors.Data were collected from 250 respondents through self administered questionnaires and SmartPLS 2.0 M3 was used to analyze the data.